Total and bioavailability concentrations of heavy metals in varieties of cooked rice, and health risk assessment - Omar, Noreen Adila (2015)
Rice in the global market is increasing over the years similarly with the rice demand. Metal contamination in rice is a rising problem recently. However, limited information regarding the bioavailability of metals contamination and its health risks after rice ingestion was known. This study aimed to determine both total and bioavailability concentrations of metals (As, Cd, Cu, Cr, Co, Al, Fe, Zn and Pb) in varieties of cooked rice samples. Moreover, this study aimed to compare bioavailability concentrations of \\etals with the rice varieties, rice grain size and origin. This study also aimed to calculate Bioaccumulation Factor (BAF) of heavy metal in varieties of cooked rice samples and assess relationships between different bioavailability metals in varieties of cooked rice. In addition, this study also identified the similarity of chemical properties among the bioavailability metals using Cluster Analysis (CA). Lastly, this study hasassessed human carcinogenic and non-carcinogenic health risks using Health Risk Assessment (HRA). About 1 kg of rice for 22 rice varieties were purchased from local groceries and supermarket based on the convenience sampling. Total metal digestion was determined by using nitric acid while bioavailability metal digestion was done using RIVM in vitro digestion model. The metal concentrations were then analysed by using Inductively Coupled Optical Emission Spectrometry Pelkin Elmer Optima 8300. Results found that Zn concentration was the highest while As was the lowest metals concentration in both total and bioavailability concentrations. All total and bioavailability concentrations of metals were below the maximum permitted levels stated by Malaysian Food Regulation (1985), FAO/WHO CAC (1984) and FAO/WHO CAC (1989). Mann-Whitney U test results (Z values) show that there was a significant difference between total and bioavailability of metals concentration (p <0.05). Kruskal walis tests results (X2 values) also show that there was a significant differences between bioavailability concentrations of metals and rice varieties (p<0.05), except for As. However, Kruskal Walis Test (X2 values) shows no significant difference between bioavailability concentrations of metals with type of rice grains size (p>0.05). Nevertheless, Mann-Whitney U results (Z values) show no significant difference between bioavailability concentrations of metals with the rice origin (p>0.05). The bioaccumulation factor (BAF) values were found in the order of Fe>Cu>Al>Zn>Cd>Co>As>Pb>Cr with parboiled rice has the highest BAF values for Fe (BAF values>1). Spearman Correlation Coefficient results (rs values) show strong positive relationships between the bioavailability metals; FeB and AlB (rs=0.83) and between AsB with PbB (rs =0.88). From Cluster Analysis (CA) results, four clusters were identified, which were Cluster 1 (Pb, As, Co, Cd, and Cr), Cluster 2 (Cu and Al), Cluster 3 (Fe), and Cluster 4 (Zn). As for HRA determination, there was no non carcinogenic health risks found (Hazard Quotient, HQ<1) for adult and children through individual heavy metal exposure. However, there was non carcinogenic health risk present among adult via the combination of these heavy metal exposures (HI > 1). On the other hand, there were potential carcinogenic health risks present for adult and children via individual intake of As (Lifetime Cancer Risk > 1x10-4). Furthermore, the values for Total Cancer Risk (TCR) for Pb and As in both adult and children were above the acceptable range (TCR > 1 x 10-4). As conclusion, this study shows that Zn was the highest metal found in 22 varieties of rice with a significant difference between total and bioavailability metal concentrations. There was also a significant difference between bioavailability metal concentration and the rice varieties. Besides, non-carcinogenic and carcinogenic health risks may posed by adult and children through their combined metal exposure in the rice.